Rifka Annisa's "Anti-Sexual Violence" Campaign and the Yogyakarta Women's Network on International Women's Day 2017 - Budi Pramono; Ayu Larassati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
IWD or International Women's Day is a day that is celebrated worldwide every 8 March. Coordinated under internationalwomenday.com, IWD is an annual campaign carried out by various women's organizations around the world. International Women's Day carries the motto "think globally, act locally". #BeBoldForChange is the theme of the 2017 International Women's Day organization. The collective action of IWD is carried out at the local level such as Yogyakarta. In Yogyakarta, collective action was carried out by a joint Yogyakarta women's organization (Yogyakarta Women's Network) by presenting various traditional performances at the zero kilometer point. They performed a dance which was inspired by the Jampi Gugat dance, which means obstacles to a better life. This dance will describe the obstacles that women face towards a better life, such as fighting sexual violence to fighting for equality in the work environment. The massive women's campaign movement in commemorating IWD proves that there are universal values that are spread and carried out in the IWD campaign until it is commemorated by all networks of women's organizations in the world. This paper will explain how the value of this campaign has influenced the local women's social movement in Yogyakarta.